Dialog o białym koniu (Bai Ma Lun) - metodologiczne problemy badań porównawczych logiki chińskiej i zachodniej - Sikora, Sławomir (Investigationes Linguisticae, 2007)
In the paper I am dealing with issues of comparative methodology in the scope of Chinese and Western logic. To exemplify the problem I chose interpretation of The White Horse Dialogue by three different sinologists. The results of the analysis carried out permits us to state that in the case of the comparative research on Chinese logic, it is rather the choice of the research method which determines the object of the examination, rather than the other way round.